SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK PENGANGKATAN KARYAWAN TETAP - Febie Elfaladonna; Andre Mariza Putra; Ria Rahmawati (AMIK Mitra Gama, 2022)
Decision support system as an interactive computer-based system that can assist decision makers in using data and models to solve unstructured problems. The management of human resources of a company greatly influences many aspects of determining the success of the work of the company. From previous research, decision support systems have been widely applied in various industries to facilitate management in making decisions. The obstacle faced by human resource management in a manufacturing industry is the criteria for hiring employees that have not been measured, so the decisions taken are still subjective. The author describes the process of determining the status of contract employees to permanent employees using the Simple Additive Weighting (SAW) method. The result of this research is a decision support system that can facilitate the management and determination of contract employees to become permanent employees based on the calculation method.